On cooperation of the universities of different countries with commercial enterprises and legal aspects of their joint innovative activities - Anisimova, Anna (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
n this article we compare and make generalizations on experiences involving cooperation between research universities in the USA, Germany, Poland and Russia and commercial enterprises in these countries. We analyze the processes of commercialization of new technologies as a promising tendency in supporting competitiveness for joint scientific and technological output of universities and companies. The experience of different countries and the economic implications for scientific, technical and intellectual advancements is considered here. We also examine the necessity for additional financial and legal regulation of research activities and defense of intellectual property.
Keywords: wspólpraca międzynarodowa; uczelnie wyższe; przedsiębiorstwa komercyjne; aspekty prawne